RFWD3 modulates response to platinum chemotherapy and promotes cancer associated phenotypes in high grade serous ovarian cancer - Taylor, Sarah J.; Hollis, Robert L.; Gourley, Charlie; Herrington, C. Simon; Langdon, Simon P.; Arends, Mark J. (Frontiers in Oncology, 2024)
Background: DNA damage repair is frequently dysregulated in high grade serous ovarian cancer (HGSOC), which can lead to changes in chemosensitivity and other phenotypic differences in tumours. RFWD3, a key component of multiple DNA repair and maintenance pathways, was investigated to characterise its impact in HGSOC.Methods: RFWD3 expression and association with clinical features was assessed using in silico analysis in the TCGA HGSOC dataset, and in a further cohort of HGSOC tumours stained for RFWD3 using immunohistochemistry. RFWD3 expression was modulated in cell lines using siRNA and CRISPR/cas9 gene editing, and cells were characterised using cytotoxicity and proliferation assays, flow cytometry, and live cell microscopy.Results: Expression of RFWD3 RNA and protein varied in HGSOCs. In cell lines, reduction of RFWD3 expression led to increased sensitivity to interstrand crosslinking (ICL) inducing agents mitomycin C and carboplatin. RFWD3 also demonstrated further functionality outside its role in DNA damage repair, with RFWD3 deficient cells displaying cell cycle dysregulation, reduced cellular proliferation and reduced migration. In tumours, low RFWD3 expression was associated with increased tumour mutational burden, and complete response to platinum chemotherapy.Conclusions: RFWD3 expression varies in HGSOCs, which can lead to functional effects at both the cellular and tumour levels.